Tetra- and triphosphane pyridine podands and their cobalt(II) and nickel(II) complexes - Heinemann, Frank Wilhelm; et al. (European Journal of Inorganic Chemistry, 2006)
The reaction of the 2,6 -diethylpyridine-derived tetraphosphane ligand C5H3N[CMe(CH2PMe2)(2)](2) (1(Me)) with nickel(II) or cobalt(II) perchlorate or tetrafluorob orate in methanol produces complexes of approximate square-pyramidal geometry (NP4 coordination). The nickel complexes are diamagnetic, with NMR spectral features ((31)p) that reflect a tetrahedral distortion of diametrically opposite phosphorus donors; this is also found in the solid state. In terms of bond lengths and angles, all complexes differ significantly from their analogues containing the phenyl- substituted ligand C5H3N[CMe(CH2PPh2)(2)](2). The ligand 1(Me) is readily and completely oxidised to the corresponding tetrakis(phosphane oxide) upon reaction with NO. Slow oxidation of the cobalt(II) tetrafluoroborate complex of 1(Me) with aerobic oxygen in acetonitrile produces a trinuclear cobalt complex containing two equivalents of partially oxidised ligand (C-2-symmetrical; donor set: [PMe2](2)[P(O)Me-2](2)). Four phosphane oxide oxygen atoms coordinate the central cobalt(II) ion in tetrahedral fashion, whereas the lateral cobalt(II) ions are in a square-pyramidal environment provided by two PMe2 donors and three acetonitrile ligands in each case. The reaction of the cobalt(II) perchlorate complex of 1(Me) with carbon monoxide gives an octahedral, 19-valence-electron dicarbonyl complex in which one of the dimethylphosphanyl groups is uncoordinated. A structural relative of 1(Me)., C5H3N[CMe(CH2PMe2)(2)][CMe2(CH2PMe2)] (2), which contains one fewer dimethylphosphanyl donor, can be prepared in a straightforward manner from 2-ethyl-6-isopropylpyridine in a four-stage process. In a series of mononuclear nickel(II) complexes, 2 employs only its three phosphane donors which, together with a monodentate ligand (acetonitrile, acetamide, or bromide), provide a tetragonal coordination environment for the metal ion which is intermediate between square planar and tetrahedral. The acetamide complex is generated from the acetonitrile complex by slow hydrolysis of the coordinated ligand. Full spectroscopic details for the complexes, as well as X-ray structure analyses, are reported.
Keywords: cobalt; nickel; N; P ligands